2008
DOI: 10.1007/s00592-007-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for elderly diabetic subjects: open label, randomized clinical trial of insulin glargine added to oral antidiabetic drugs versus increased dosage of oral antidiabetic drugs

Abstract: Glycemic control in elderly persons with type 2 diabetes mellitus (T2DM) is challenging because they are more likely to have other age-associated medical conditions and to experience hypoglycemia during intensive therapy. A best therapeutic strategy for these patients has not yet been defined. We investigated the efficacy and safety of adding once-daily insulin glargine to patients' current oral antidiabetic drugs (OAD) regimen, compared to increasing the OAD doses. The study enrolled patients aged 65 years or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 19 publications
1
14
0
4
Order By: Relevance
“…The finding of a low risk of hypoglycemia associated with insulin use is in line with other studies that reported lower hypoglycemia risk with insulin added to OADs compared with OADs alone 29 or no increase in hypoglycemia with insulin compared with OADs 30,31 . This finding has implications for programs and interventions focused on reducing barriers to RAI initiation and persistence, as the fear of adverse effects (such as hypoglycemia) is one of the reasons for not initiating insulin therapy among both physicians and patients 3235 .…”
Section: Discussionsupporting
confidence: 90%
“…The finding of a low risk of hypoglycemia associated with insulin use is in line with other studies that reported lower hypoglycemia risk with insulin added to OADs compared with OADs alone 29 or no increase in hypoglycemia with insulin compared with OADs 30,31 . This finding has implications for programs and interventions focused on reducing barriers to RAI initiation and persistence, as the fear of adverse effects (such as hypoglycemia) is one of the reasons for not initiating insulin therapy among both physicians and patients 3235 .…”
Section: Discussionsupporting
confidence: 90%
“…The FPG levels were similar at baseline and endpoint for the different types of insulin [19]. A substantial reduction in BG levels was reported when insulin was added to OADs compared to OADs alone [22]. QoL/TS.…”
Section: Initiationmentioning
confidence: 79%
“…For elderly diabetic patients with inadequately controlled hyperglycemia, patients with early combinations of basal insulin had better glycemic control and less hypoglycemia than titration of oral antidiabetic drugs 175. In diabetic elders with poorly controlled glycemia, insulin therapy did not result in higher hypoglycemia events if glycemic targets were less stringent 176.…”
Section: Options Of Therapy In Elderly Patientsmentioning
confidence: 99%